Khitan dalam Literatur Hadis Hukum - Nurasiah Nurasiah (Universitas Islam Negeri Jakarta, 2015)
What was found in this paper strengthen Syaltut Mahmud statement and some other scholars that the orders circumcision, for both men and women, not relying directly on religious scripture text, because no one else valid hadith regarding circumcision command. The arguments presented cleric who require circumcision is very weak. According to Mahmud Syaltut, the command of circumcision in Islam actually be accommodated only through the rule of jurisprudence that injure members of the living body (in this case circumcision) is allowed if it there is the benefit derived from it.DOI: 10.15408/ajis.v15i1.2851